2007
DOI: 10.1103/physrevlett.99.089202
|View full text |Cite
|
Sign up to set email alerts
|

Cantonet al.Reply:

Abstract: Canton et al. Reply: In the preceding Comment, Fortune and Sherr (FS) agree with our prediction on the existence of three narrow odd-parity resonances in 15 F, finding them within the same excitation range and having the same spinparity and level ordering. Their argument, based upon a very different approach from ours, concerns some differences in the resonance centroids and widths. They conclude that the energies and widths of these narrow resonances might be considerably different from what we found.FS comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
178
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 32 publications
(185 citation statements)
references
References 3 publications
6
178
1
Order By: Relevance
“…Thus, the odd-parity 15 F states may not be as narrow as predicted in Refs. [6,7]. Such a phenomenon may be general for nuclei beyond the proton drip line, where 1p and 2p thresholds are very low.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the odd-parity 15 F states may not be as narrow as predicted in Refs. [6,7]. Such a phenomenon may be general for nuclei beyond the proton drip line, where 1p and 2p thresholds are very low.…”
mentioning
confidence: 99%
“…Recently, Canton et al [6] suggested that some unbound states could exist as very narrow resonances. Using multichannel algebraic scattering (MCAS) theory, Canton et al predicted three odd-parity states in 15 − , with the widths of only a few keV.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 F is one such case [3]. The A = 7 system also has been considered with a unique nuclear potential, and the level structures of 7 He, 7 Li, 7 Be, and 7 B have been obtained [2].…”
Section: Introductionmentioning
confidence: 99%
“…We have also used the scheme to consider low energy properties of 3 H-and 3 He- 4 He scattering to correlate different views of the spectra of 7 Li and 7 Be. The di-cluster structure of 7 Be that results has then been used to evaluate the astrophysical S-factor for the radiative capture of 3 He by 4 He.…”
Section: Introductionmentioning
confidence: 99%